Toxicity Study on Alkaloid-Rich Fraction of Detarium microcarpum (Fabaceae) Stem Bark in Wistar Rats - Ahmad M. M; Maje M. I.; Aminu U. K; Abba M. U (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Several studies reported the toxicity profile of the stem bark extract of Detarium microcarpun plant. However, no available data on the toxicity profile of the various fractions of its crude extract which gives baseline for isolation of lead compounds. The aim of the study is to evaluate the effect of 28-day repeated oral administration of alkaloid-rich fraction of Detarium microcarpum stem bark extract on biochemical parameters in Wistar rats. Wistar rats were divided into four groups of five animals each and administered different doses (250, 500 and 1000 mg/kg) of alkaloid-rich fractions via oral route. Body weight changes, relative organ weights (liver, kidney, spleen, heart), serum liver biomarkers (ALT, AST, ALP), liver function parameters (total protein, albumin), kidney function parameters (urea, creatinine, BUN), electrolytes (Na, HCO, K, Cl), and oxidative stress parameters (MDA, CAT, SOD, GPx, LDH, GGT, GHS) were measured using standard techniques. The body weight changes insignificantly (p˃0.05) for rats in the acute toxicity study where the weight increases after administration of the alkaloid-rich fractions of D. microcarpum stem bark at a single oral dose of 5000 mg/kg from day 1 to day 14. The same was observed when different doses of the fraction were administered for 28 days. The result indicated the no significant (P˃0.05) organ weight (%) for liver, kidney, spleen, brain and heart. There was no significant (P˃0.05) increase in serum ALT, AST, ALP, TP, ALB, Urea, Creatinine, MDA, CAT, SOD, GPx, LDH, GGT GHS electrolytes and hematological parameters levels in the normal control group compared to other groups. Administration of 250, 500 and 1000 mg/kg of alkaloid-rich fractions of D. microcarpum stem bark for 28 days showed congested central vein and the sinusoids and the hepatocytes appeared normal. The kidney section of rats from all the groups shows normal appearance of the glomerulus, Bowman’s capsule and the tubules. The alkaloid-rich fraction of Detarium microcarpum stem bark produces no effect on body and organ weights, biochemical activities and oxidative stress parameters in Wistar rats, suggesting its relative safety.